Impaired Platelet Function in Sept8-Deficient Mice In Vitro - Neubauer, Katharina; Jurk, Kerstin; Petermann, Victoria; Kumm, Elena; Zieger, Barbara (Thrombosis and Haemostasis, 2020)
Septins (Septs) are a widely expressed protein family of 13 mammalian members, recognized as a unique component of the cytoskeleton. In human platelets, we previously described that SEPT4 and SEPT8 are localized surrounding α-granules and move to the platelet surface after activation, indicating a possible role in platelet physiology. In this study, we investigated the impact of Sept8 on platelet function in vitro using Sept8-deficient mouse platelets. Deletion of Sept8 in mouse platelets caused a pronounced defect in activation of the fibrinogen receptor integrin αIIbβ3, α-granule exocytosis, and aggregation, especially in response to the glycoprotein VI agonist convulxin. In contrast, δ-granule and lysosome exocytosis of Sept8-deficient platelets was comparable to wild-type platelets. Sept8-deficient platelet binding to immobilized fibrinogen under static conditions was diminished and spreading delayed. The procoagulant activity of Sept8-deficient platelets was reduced in response to convulxin as determined by lactadherin binding. Also thrombin generation was decreased relative to controls. Thus, Sept8 is required for efficient integrin αIIbβ3 activation, α-granule release, platelet aggregation, and contributes to platelet-dependent thrombin generation. These results revealed Sept8 as a modulator of distinct platelet functions involved in primary and secondary hemostatic processes.
Keywords: platelets; septins; exocytosis; glycoprotein VI; coagulation